Security Study of Software-Defined Enterprise Data Center Network - Wenmao Liu (Dianxin kexue)
Security threats of novel data center using software-defined networking were analyzed, and then three protection phases for defending were proposed, which solved unique problems and overcame current security product defects, and finally a software-defined security architecture to defend various quick and advanced attacks was designed.